Analisis Gradasi Penggunaan Material Agregat Base Class A Spesifikasi BinaMarga 2010 Rev 3 Proyek Pelebaran Jalan Sp. Ujung Aji – Batas Kota Kabanjahe - Brian Baya Sembiring. ST; Parada Afkiki Eko Saputra, ST,MT (Universitas Quality, 2019)
Road is a land transportation infrastructure that covers all parts of the road, including complementary buildings and equipment intended for traffic. Road Structure Improvement is one project that aims to improve the quality of roads. As the object of work to be studied is the widening of the sp. Ujung Aji - Limits of the City of Kabanjahe. Road construction with a flexible layered pavement with cover or without overlays is usually often damaged such as: cracks, hollows, bumps on the road surface. In other conditions it is often seen that the grooves of the former water flow to the subgrade are visible. The situation is more extreme and often occurs, namely the road surface peels to reach the foundation layer, so that the aggregate looks scattered. This study uses the direct observation method in the widening project of Jalan Simpang Ujung Aji - Bts. Kabanjahe City. This research was carried out at the time of laying and compaction of the bottom road foundation layer such as Base B and Base A. Activities carried out included data collection, data processing, analysis and observations in the Laboratory. The results of the filter analysis of rough gradations are good, which is in the middle between the given gradation boundaries, does not coincide and does not come out of the given gradation limit. Based on aggregate filter analysis data, it can be concluded that the results of the gradation of aggregate class A percent are retained and passed the filter in accordance with the general specifications of Bina Marga 2010 revision 3 and according to class A aggregate planning. the specimen is completely waterless, so the weighing results in the right balance.